Search for Saturn's X‐ray aurorae at the arrival of a solar wind shock. Issue 5 (22nd May 2013) - Branduardi‐Raymont, G.; Ford, P. G.; Hansen, K. C.; Lamy, L.; Masters, A.; Cecconi, B.; Coates, A. J.; Dougherty, M. K.; Gladstone, G. R.; Zarka, P.
Abstract : [1] After a decade of observations, evidence for X‐ray auroral emission from Saturn has yet to be found. By analogy with processes known to take place on Jupiter, Saturnian X‐ray aurorae may be expected to be powered by charge exchange (CX) between energetic ions and the planet's atmospheric neutrals; if the ions are of solar origin, the emission should be brightest during episodes of enhanced solar wind (SW). We have explored this possibility by propagating SW parameters measured near the Earth to Saturn, and triggering X‐ray observations at the time SW enhancements were expected to reach the planet. This was done in April–May 2011 with the Chandra X‐ray Observatory, and we report on two observations carried out at the time when a significant SW disturbance reached Saturn, as indicated by Cassini magnetic field, plasma and radio measurements: variability is observed between the two Chandra datasets, but we do not find evidence for X‐ray brightening in the auroral regions. The variability can be explained by scattering of solar X‐rays in Saturn's atmosphere during an episode of solar X‐ray flaring. We conclude that the strength of any CX auroral X‐ray emission on Saturn was below Chandra's detectability threshold. By‐products of this investigation are stringent upper limits on the X‐ray emission of Titan and Enceladus. The Cassini measurements concurrent with the Chandra observations confirm and pinpoint temporally the arrival of the SW enhancement at Saturn. SW propagation predictions are a useful tool for investigating and interpreting the effects of SW interactions with planetary environments. Key Points: Predict solar wind shock arrival at Saturn and search for X‐ray aurora Validate solar wind propagation predictions with Cassini observations Origin of Saturn's rings X‐ray emission